2007
DOI: 10.1063/1.2435980
|View full text |Cite
|
Sign up to set email alerts
|

Direct probe of excitonic and continuum transitions in the photocurrent spectroscopy of individual carbon nanotube p-n diodes

Abstract: The authors show that a carbon nanotube p-n diode is a very sensitive probe of optical transitions in individual single-walled carbon nanotubes. In the photocurrent spectra, an alternating sequence of resonant peaks from dissociation of excitons and exciton-phonon bound states, for the lowest and higher electronic subbands, is observed. At an intermediate energy, the onset of continuum is observed that allows measurement of exciton binding energies. Both the binding energy and the onset of continuum follow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…[49,66,67] In 2013, Barkelid et al systematically studied the photocurrent generation of SWCNT p-n diodes. [67] Their studies revealed that the photocurrent generation of metallic nanotubes was due to thermal effects, while the photovoltaic effect was responsible for the photocurrent generation in semiconducting nanotubes.…”
Section: Photodiodes Based On Individual Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49,66,67] In 2013, Barkelid et al systematically studied the photocurrent generation of SWCNT p-n diodes. [67] Their studies revealed that the photocurrent generation of metallic nanotubes was due to thermal effects, while the photovoltaic effect was responsible for the photocurrent generation in semiconducting nanotubes.…”
Section: Photodiodes Based On Individual Swcntsmentioning
confidence: 99%
“…Later, numerous studies put attention on the spatially-and spectrally-resolved photocurrent of individual CNT devices to explore the electron-hole pair generation and separation in semiconducting SWCNTs [46,47,48,49] and the nanophysics of individual CNT devices such as the formation of Shottky barriers at the CNT-metal electrode interfaces. [50,51,52] Although photoconductors based on individual CNTs are a useful platform to investigate the photophysics of nanodevices, the signal is too weak for practical photodetection due to the small absorption cross section.…”
Section: Cnt Photoconductorsmentioning
confidence: 99%
“…For wavelengths of 900 nm and longer a large selection of carbon nanotubes are available with E11 at these wavelengths. The FWHM of the E11 is typically of the order of 50 meV, 17,18 and the density of carbon nanotube chiralities with the E11 above 900 nm is sufficiently high, with respect to the absorption linewidth, to readily cover the infra-red part of the solar spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…After locating the position of the nanotube diode, we performed photocurrent spectroscopy 4,14,17 to identify the optical transitions in the carbon nanotube. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Free electron/ hole pairs excited by photons can be either separated by an externally applied voltage [32], by internal fields at the Schottky barriers [33,34], at p-n junctions [35][36][37] or at defects [38,39]. A photocurrent [32] or a photovoltage [33][34][35][36][37][38][39] can be generated.…”
Section: Cntsmentioning
confidence: 99%